Equality, Priority and Person-Affecting Value - Persson, Ingmar (Ethical theory and moral practice, 2001)
Derek Parfit has argued that (Teleological) Egalitarianism is objectionable by breaking a person-affecting claim to the effect that an outcome cannot be better in any respect - such as that of equality - if it is better for nobody. So, he presents the Priorty View, i.e., the policy of giving priority to benefiting the worse-off, which avoids this objection. But it is here argued, first, that there is another person-affecting claim that this view violates. Secondly, Egalitarianism can be construed as person-affecting in a weaker sense. Thirdly, it is possible to construct a Relational version of the Priority View which incorporates the Egalitarian value of just equality in this sense. Two reasons are given for why this Relational View and Egalitarianism are superior to the Parfitian Absolute Priority View. However, no attempt is made to abjudicate between the first two views, the main point being that they both accept the value of just equality in the same sense.